2022
DOI: 10.2991/absr.k.220309.068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physicochemical Properties and Antioxidant Activity of Chicken Meatballs by Substitution of Tapioca Flour with Purple Sweet Potato

Abstract: Purple sweet potatoes are widely used as a source of antioxidants and natural dyes in food products. This study aimed to evaluate the physicochemical properties and antioxidant activity of substitution of tapioca flour with purple sweet potato flour. The treatments employed were the substitution of tapioca flour (T) with purple sweet potato (P) with a ratio of 20:0; 15:5; 10:10; 5:15, and 0:20 (meat weight basis). Variables measured were nutrient content, pH, cooking loss, water holding capacity (WHC), Colour,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Amer et al [13] found that the inclusion of anthocyanin-rich roselle, Hibiscus sabdariffa L. extract, could improve chicken antioxidant potential by increasing serum total antioxidant capacity (TAC) and superoxide dismutase (SOD) concentrations and by decreasing serum malondialdehyde (MDA) level. Additionally, Hajrawati et al [14] demonstrated that anthocyanin-rich purple sweet potato flour could increase the cooking loss, anthocyanin content, redness, and scavenging activity of chicken meatballs.…”
Section: Introductionmentioning
confidence: 99%
“…Amer et al [13] found that the inclusion of anthocyanin-rich roselle, Hibiscus sabdariffa L. extract, could improve chicken antioxidant potential by increasing serum total antioxidant capacity (TAC) and superoxide dismutase (SOD) concentrations and by decreasing serum malondialdehyde (MDA) level. Additionally, Hajrawati et al [14] demonstrated that anthocyanin-rich purple sweet potato flour could increase the cooking loss, anthocyanin content, redness, and scavenging activity of chicken meatballs.…”
Section: Introductionmentioning
confidence: 99%